Invisible axion and neutrino masses - Dias, Alex G.; Pleitez, V. [UNESP] (My University, 2006)
We show that in any invisible axion model due to the effects of effective nonrenormalizable interactions related to an energy scale near the Peccei-Quinn, grand unification or even the Planck scale, active neutrinos necessarily acquire masses in the sub-eV range. Moreover, if sterile neutrinos are also included and if appropriate cyclic ZN symmetries are imposed, it is possible that some of these neutrinos are heavy while others are light. © 2006 The American Physical Society.